Konstruksi Biaya Transaksi dan Prinsip Ekonomi Islam dalam Agroindustri Kakao - Maharani, Rivana; Nurlaili, Nurlaili; Hasimi, Diah Mukminatul (Kartika: Jurnal Studi Keislaman, 2025)
Indonesia as one of the world's largest cocoa producers faces competitiveness challenges due to declining production and low added value due to the dominance of exports in the form of raw beans. This study aims to analyze the determinants of transaction costs among cocoa farmers in Sukadana Subdistrict, East Lampung Regency with an Islamic economic approach. The study used a quantitative method through a cross-sectional survey with primary data from 99 cocoa farmers selected by purposive sampling. Data analysis used ordinary least square multiple regression to test the influence of frequency, institutional, social capital, trust, and extension variables on transaction costs. The results showed that trust and frequency of interaction had a significant positive effect on transaction costs, while institutionalization and social capital were not significant. The study concluded that the frequency of transaction costs can be minimized by eliminating transportation costs from farmers to the market, as well as the importance of good communication between administrators and members in the institutional aspect. The contribution of this research is the understanding that transaction costs in Islamic economics include not only financial aspects but also social aspects such as justice, trade balance, and business ethics according to Islamic principles.